Penyuluhan Keluarga Berencana sebagai Upaya Peningkatan Pemahaman Masyarakat tentang Perencanaan Keluarga di Kecamatan Libureng, Kabupaten Bone - Mildayanti; Dwiyanti; Yulnita Muchtar; Damas Gianlugi Alrizqi; Nurul Haeriyah Ridwan (ABDI SAMULANG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract The Family Planning (KB) program is a strategic government initiative to realize quality families through birth spacing and improved reproductive health. Limited community understanding of contraceptive methods remains an obstacle to achieving program targets, particularly in agrarian areas such as Libureng District, Bone Regency. This community service activity aimed to improve public understanding of family planning through counseling conducted in collaboration between lecturers of Universitas Negeri Makassar and the local BKKBN. The method consisted of preparation, interactive counseling implementation, and evaluation stages, targeting fertile-age couples, family planning cadres, and sub-district officials totaling approximately 40 participants. Results showed improved participant understanding of contraceptive methods, the benefits of Long-Term Contraceptive Methods (LTCM), and a more open attitude toward the KB program. This activity confirms that synergy between higher education and government institutions is an effective strategy for supporting the Bangga Kencana program at the sub-district level.